Fuzzy prolog with default knowledge - Vaucheret, Claudio A. (2004)
In omplete information is a problem in many aspe ts of a tual environments. Further- more, in many s enarios the knowledge is not represented in a risp way. It is ommon to nd fuzzy on epts or problems with some level of un ertainty. This work extends the semanti s and implementation of fuzzy prolog presented in [VGM02, GMV04℄ in order to in lude Default Knowledge apability. The new semanti allows non-uniform default assumptions and has Closed World Assumption (CWA) and Open World Assumption (OWA) as parti ular ases.